La aplicación de las tecnologías de la información y la comunicación (tic), como recurso didáctico y su incidencia en el proceso de enseñanza - aprendizaje de la matemática en los estudiantes de primer año de bachillerato general unificado del colegio de bachillerato Beatriz Cueva de Ayora de la ciudad de Loja, periodo 2016 – 2017. Lineamientos alternativos. - Lojan Quirola, Edgar Leonardo (2018)
The present work was aimed at investigating: THE APPLICATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES (ICT), AS A TEACHING RESOURCE AND ITS INCIDENCE IN THE TEACHING PROCESS - LEARNING OF MATHEMATICS IN THE STUDENTS OF THE FIRST YEAR OF UNIFIED GENERAL HIGH SCHOOL OF THE SCHOOL “BEATRIZ CUEVA DE AYORA” OF THE CITY OF LOJA, PERIOD 2016 - 2017. The objective of the research was to determine the didactic resources used by teachers in the teaching of mathematics in the first year of unified general high school, to diagnose the difficulties that arise in the learning of mathematics in the first year of unified general high school, propose alternative guidelines to improve the teaching-learning process of Mathematics with the support of ICT. The hypothesis referred to the fact that the application of Information and Communication Technologies (ICT), as a didactic resource, significantly affects the teaching - learning process of mathematics in the first year of unified general high school of the School “Beatriz Cueva de Ayora” of the city of Loja, period 2016 - 2017. The main methods used were scientific, inductive, deductive, analytical, synthetic and statistical. With respect to the techniques and instruments used, we have the bibliographic technique, direct observation technique and application of surveys directed to both students and teachers; this served for the verification of the hypothesis. The design is of a qualitative nature, it dispenses with the experimentation itself and is descriptive. , whose synthesis led to the determination of pertinent conclusions and recommendations. The results show that although ICTs are an important didactic resource in the teaching - learning process of students, this study shows that in the classroom those involved do not use them for said process, therefore, the general Hypothesis is rejected; although a high percentage of both teachers and students believe that the implementation of ICT in the teaching-learning process would significantly help to make the classes more active and participatory.